Factors associated with eating disorders in adolescents: a systematic review - Suarez-Albor, Candy Laurine; Galletta, Maura; Gómez-Bustamante, Edna Margarita (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: The World Health Organization has placed eating disorders among the priority mental illnesses for children and adolescents given the risk they imply for their health. Recognizing the risk factors associated with this problem can serve as the basis for the design of timely and effective interventions. The objective of the study was to identify the factors associated with eating behavior in adolescents through a systematic review.Methods: Systematic review. Search of the literature in the bibliographic sources CINAHL, CUIDEN, Pubmed, Dialnet, SCIELO and Science Direct. The search was conducted in October and November 2020. The search terms were Eating Disorders, Food Intake, and Adolescents. The evaluation of the methodological quality was carried out using a specific guide for observational epidemiological studies. A narrative synthesis of the findings was made. Additionally, the vote counting and sign test technique was applied.Results: 25 studies were selected. The associated factors were body dissatisfaction, female gender, depression, low self-esteem, higher BMI that increases the risk of eating disorders.Conclusions: a high impact of psychological factors was observed. These should be considered in the design of effective interventions to prevent this disease, although the search needs to be broadened to identify larger and more complex studies that allow for a more comprehensive review.